مساهمة العلاقات العامّة في دعم الاتّصالات التّسويقيّة البيئيّة المتكاملة وتحقيق فعاليّة الأداء البيئي للمنظّمات الاقتصاديّة (El-Wahat Journal for Research and Studies, 2021)
The Multiple Issues Of The Environment Are Presented  As A Strategic Imperative, In Order To Realize The Dimensions Of Sustainable Development, Being A Common Human Heritage And An Integral Part Of Human Rights; International Forums Have Embarked On A Number Of Conventions, Policies And Strategies To Ensure This Right. Economic Institutions, As One Of The Effective Members Responsible For The Clear And Visible Impact Of Their Activities On The Environment, Had To Reassess Their Overall Policies To Be More Committed To Their Environmental And Social Responsibilities By Incorporating Considerations That Would Enable Them To Correct Their Performance In Response To Requirements Imposed By International And Domestic Legislation On Environmental Protection.This Is Linked To The Extent To Which They Are Able To Establish The Necessary Foundations That Limit The Impact Of Their Activities On The Environment In Order To Harmonize With Their Surroundings, Preserve Their Image And Ensure Their Survival And Continuity, And Public Relations Are An Important Tributary To This End.Hence, This Research Paper Is Important To Highlight The Position And Role Of Public Relations In Supporting Integrated Environmental Marketing Communications As A Mechanism Within The Environmental Marketing Mix, As Well As Focus On The Public Relations Communication Function In Managing The Image And Reputation Of The Organization, Thereby Contributing, Strengthening And Activating Its Environmental Performance. Keywords -  Public Relations-  Integrated Marketing Communications- Environmental Performance - Environmental Responsibility- Mental Image- The Reputation Of The Organization.